Clinical Assessment and Differential Diagnosis of Pediatric Pseudotumor Cerebri Syndrome: Pearls and Pitfalls - Fokoloros, Christos; Spyridou, Christina; Kinali, Maria (Journal of Pediatric Neurology, 2015)
Pseudotumor cerebri syndrome (PTCS) is defined by the presence of elevated intracranial pressure in the setting of normal brain parenchyma and normal cytologic and chemical analyses of the cerebrospinal fluid. Pathophysiology of this syndrome remains unclear, while its incidence may be potentially rising in children. The presenting signs and symptoms of PTCS are heterogeneous to usually include headache, papilledema, and visual disturbances (i.e., vision loss or double vision). The clinical features of PTCS in children have changed over the years, making the diagnosis challenging in some cases. Young children may present with atypical symptoms, such as those mimicking a posterior fossa tumor. There are reports of PTCS in children in the absence of headache. Papilledema, considered the acute hallmark of PTCS at onset, can also be absent. It is thus important for pediatricians to recognize atypical presentations especially as previous studies have suggested children presenting with headache in the absence of papilledema or those with papilledema in the absence of any other clinical signs may have increased risk of developing visual constriction deficits and permanent loss of vision, respectively. Moreover, many conditions in the pediatric age group may mimic PTCS, such as migraine and tension headaches. Cerebral venous sinus thrombosis and some neoplastic processes such as gliomatosis cerebri and leptomeningeal spread of hematologic malignancies are known to augment intracranial pressure and have to be carefully excluded. To avoid misdiagnosis and potential long-term sequel, a thorough clinical assessment is crucial to promptly and correctly recognize PTCS.
Keywords: idiopathic intracranial hypertension; pseudotumor cerebri; children; differential diagnosis